Internal switching and backward inhibition in depression and rumination. (30th September 2016) - Chen, Xiao; Feng, Zhengzhi; Wang, Tao; Su, Hong; Zhang, Lihong
Abstract: Prior research has suggested that impairments of switching abilities are associated with depression as well as rumination. Backward inhibition (BI) refers to the ability to inhibit the processing of previously relevant information and is demonstrated to be one of the key mechanisms underlying switching abilities. However, the association between BI in internal switching and depression/rumination remains uninvestigated. To examine this association, a modified Internal Shifting Task (IST) was administered to a sample of dysphoric and healthy control undergraduates. Results showed that depressive symptoms were not associated with difficulties in switching among subjects held in working memory, while trait ruminators performed poorly in switching internally. Surprisingly, no association between BI in internal switching and rumination/depressive symptoms was found. These findings indicate that rumination is characterized by poor performance in internal switching, but this deficit is not associated with BI. Highlights: The original Internal Shifting Task (IST) was modified. Trait ruminators have a deficit in the internal switching ability. Backward inhibition (BI) is not associated with depressive symptoms or rumination. The dysphorics exhibit a general delay in the reaction times.